Bank Directors' Perceptions of Expanded Auditor's Reports. Issue 2 (22nd March 2016) - Boolaky, Pran Krishansing; Quick, Reiner
Abstract : Subsequent to the financial crisis, standard setters developed suggestions for enhancing the audit function, in order to increase financial stability. One related idea is to expand the audit report disclosed to the public, to ensure that it is fit for purpose. This study investigates the impact of expanded audit reports, namely information on the assurance level, materiality levels and key audit matters (KAM), on bank director perceptions of the quality of the financial statements, the audit and the audit report, as well as on their credit approval decisions. We conduct an experiment involving a sample of 105 bank directors and use ANCOVA to determine the predictors of bank director perceptions and decisions. Our findings suggest that disclosing the assurance level has a significantly positive impact. In contrast, we cannot demonstrate a material effect of expanding the audit report to include the materiality level or KAM. As a consequence, standard setters should carefully analyse the effect of additional information before making decisions on expanding the content of the audit report. Such expansions are not necessarily perceived as useful by stakeholders.